Defect Detection in Plate Structures using Wavelet Transformation - KNITTER-PIĄTKOWSKA, Anna; GUMINIAK, Michał Jan (Engineering Transactions, 2016)
This paper is concerned with defect detection in plate structures while considering the influence of external loads. The examined structures are based on Kirchhoff plate structures. Rectangular plate structures are considered. Plate bending is described using the boundary element method. The boundary and boundary-domain integral equations are formulated in a modified, simplified approach without the need of using a value known from the classical theory of Kirchhoff plate bending. Constant-type boundary elements in a non-singular approach are introduced. The plates are loaded with a single static concentrated force or dynamic moving force. External loading is applied at selected points along the direction parallel to one dimension of the plate. Defects are introduced by additional edges forming slots or holes in relations to the basic plate domain. Deflections and curvatures are taken into account as structural responses. Analysis of structural responses is conducted using the signal processing tool of wavelet transformation in its discrete form.